Early Influences of Microbiota on White Matter Development in Germ-Free Piglets - Ahmed, Sadia; Travis, Sierrah D.; Díaz-Bahamonde, Francisca V.; Porter, Demisha D. L.; Henry, Sara N.; Mykins, Julia; Ravipati, Aditya; Booker, Aryn; Ju, Jing; Ding, Hanzhang; Ramesh, Ashwin K.; Pickrell, Alicia M.; et al. (Frontiers in Cellular Neuroscience, 2021)
Abnormalities in the prefrontal cortex (PFC) as well as the underlying white matter (WM) tracts lie at the intersection of many neurodevelopmental disorders. The influence of microorganisms on brain development has recently been brought into the clinical and research spotlight as alterations in commensal microbiota are implicated in such disorders, including autism spectrum disorders, schizophrenia, depression, and anxiety via the gut-brain-axis. In addition, gut dysbiosis is common in preterm birth patients who often display diffuse WM injury and delayed WM maturation in critical tracts including the PFC and corpus callosum. Microbial colonization of the gut aligns with ongoing postnatal processes of oligodendrogenesis and the peak of brain myelination in humans; however, the influence of microbiota on gyral WM development remains elusive. Here, we develop and validate a neonatal germ-free swine model to address these issues, as piglets share key similarities in WM volume, developmental trajectories, and distribution to humans. We find significant region-specific reductions, and sexually dimorphic trends, in WM volume, oligodendrogenesis, and mature oligodendrocyte numbers in germ-free piglets during a key postnatal epoch of myelination. Our findings indicate that microbiota play a critical role in promoting WM development during early life when the brain is vulnerable to environmental insults that can result in an array of disabilities manifesting later in life.